Burnout: The resident evil — Perspectives from the horses' mouth! - Pallavi Priyam; Abheek Sil (Indian Dermatology Online Journal, 2020)
Burn-out is a syndrome conceptualized as resulting from chronic workplace stress that has not been successfully managed. It is characterized by three dimensions- (1) feelings of energy depletion or exhaustion, (2) increased mental distance from one's job, or feelings of negativism or cynicism related to one's job and (3) reduced professional efficacy. Any profession where a certain amount of emotional work and empathy are expected renders a person vulnerable to being burned out. Resident doctors, who play the role of a primary care-giver and spend a great deal of time with patients, are most prone to suffer. However, early identification and necessary intervention would go a long way in making the three formative years of a doctor's life more worthwhile.